Role of Sonographic Measurement of Fetal Foot Length in Estimating Gestational Age: A Hospital Based Study in South Punjab - Nadeem, Syed Farrukh; Babar, Taimur Hussain; Khan, Amir Ali; Asim, Muhammad Umar; Malik, Muhammad Jalil; Ahmad, Muhammad Iftikhar (Pakistan Armed Forces Medical Journal, 2022)
OBJECTIVE:  To highlight the usefulness of ultrasonographic measurement of fetal foot length in determining fetal gestational age. STUDY DESIGN: Prospective validation studyPLACE AND DURATION OF STUDY:   Radiology Department Combined Military Hospital Bahawalpur from 01July 2020 to 31Dec 2020.METHODOLOGY:    Women referred from our obstetrics OPD for antenatal ultrasound between 16 to 40 weeks were scrutinized through inclusion and exclusion criteria for selection in the study.  Record of their age, parity, gestational age by LMP and sonographic measurement of fetal foot length were endorsed on a study proforma. After the end of study period, the data was entered in SPSS version 20 to measure Pearson correlation coefficient and R2 values for highlighting the correlation between two variables. P value < 0.01 is taken as significant.   RESULTS:  A total of 153 patients were included in the study. Mean age of patients in our study is 28.64 years and second parity is most frequent being 41.8%. Data entered in SPSS version 20 for regression analysis. Pearson correlation coefficient (R) is 0.988 and R2 value is 0.977 (P- 0.000) which shows powerful linear correlation between our two variables. CONCLUSION:  The results of our study shows excellent reliable linear correlation between fetal foot length and gestational age by LMP. Therefore, the fetal foot length so measured by ultrasonography can be used confidently for determination of gestational age in routine or when other ultrasonographic measurement parameters become unreliable.KEYWORDS:  Fetal foot length, Gestational age, Ultrasonographic age estimation.